Recent Advances in Chiral Analysis of Proteins and Peptides - Morvan, Marine; Mikšík, Ivan (MDPI, 2021)
Like many biological compounds, proteins are found primarily in their homochiral form. However, homochirality is not guaranteed throughout life. Determining their chiral proteinogenic sequence is a complex analytical challenge. This is because certain D-amino acids contained in proteins play a role in human health and disease. This is the case, for example, with D-Asp in elastin, beta-amyloid and alpha-crystallin which, respectively, have an action on arteriosclerosis, Alzheimer's disease and cataracts. Sequence-dependent and sequence-independent are the two strategies for detecting the presence and position of D-amino acids in proteins. These methods rely on enzymatic digestion by a site-specific enzyme and acid hydrolysis in a deuterium or tritium environment to limit the natural racemization of amino acids. In this review, chromatographic and electrophoretic techniques, such as LC, SFC, GC and CE, will be recently developed (2018-2020) for the enantioseparation of amino acids and peptides. For future work, the discovery and development of new chiral stationary phases and derivatization reagents could increase the resolution of chiral separations.
Nové poznatky v oblasti chirálních separací bílkovin a peptidů
Keywords: chiral separation; proteins; peptides; D-amino acids; chirální separace; bílkoviny; peptidy; D-aminokyseliny